Blood volatile organic compounds as potential biomarkers for poly cystic ovarian syndrome (PCOS): An animal study in the PCOS rat model. Issue 226 (February 2023) - Ataabadi, Mahmoud Sadeghi; Bahmanpour, Soghra; Yousefinejad, Saeed; Alaee, Sanaz
Abstract: Polycystic ovary syndrome (PCOS) as a common metabolic and endocrinological disorder can affect the metabolic profile in biological fluids. We studied the profile of blood volatile organic compounds (VOCs) in rats with PCOS and controls to identify potential specific biomarkers of blood VOCs in PCOS rats. For this purpose, 30 female adult Wistar rats were assigned to two groups: control and PCOS groups. PCOS model was induced using letrozole gavage (1 mg/kg) for 21 days. The rats in the control group received water of the same volume for 21 days. During treatment, a collection of vaginal smears was done every day for estrus cycle determination and weight was measured weekly. On the day after the last administration of letrozole, the rats were killed and their blood and ovaries were collected. Testosterone levels and histologic changes in ovaries were examined. Also, headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC–MS) analyzed the VOCs in the blood of PCOS and control rats. Multivariate and univariate statistical analyses were used to find the potential biomarkers for a rat model of PCOS. Weight gain, ovarian and vaginal pathological alteration, as well as hyperandrogenemia, confirmed the successful induction of the PCOS in rats. The results of blood VOCs analysis showed that nine VOCs were significantly elevated and one VOC decreased in the PCOS group than the control group (P < 0/05). The partial least-squares discriminant analysis (PLS-DA) and principal component analysis (PCA) showed good separation of VOCs between the PCOS rats and the control group. The 4-ethylphenol and capric (decanoic) acid were selected as the potential biomarkers for PCOS diagnosis in the blood of the PCOS rats. The blood of PCOS rats had a specific profile of VOCs, which could be detected by GC-MS analysis. These findings can pave the way for further studies towards developing a new screening method for PCOS detection and studying their pathology, based on VOCs analysis. Highlights: Polycystic ovary syndrome (PCOS) can affect the metabolic profile in biological fluids of rats. Volatile organic compounds (VOCs) in blood of PCOS rats are potential biomarkers for discrimination of PCOS samples. 4-ethylphenol and capric acid can be the potential biomarkers of PCOS.